'Meaning-dawning' in Wittgenstein's Notebooks: a Kierkegaardian reading and critique. Issue 3 (4th May 2018) - Schönbaumsfeld, Genia
ABSTRACT: In this paper, I am going to propose a new reading of Wittgenstein's cryptic talk of 'accession or loss of meaning' (or the world 'waxing and waning' as a whole) in the Notebooks that draws both on Wittgenstein's later work on aspect-perception, as well as on the thoughts of a thinker whom Wittgenstein greatly admired: Søren Kierkegaard. I will then go on to argue that, its merits apart, there is something existentially problematic about the conception that Wittgenstein is advocating. For the renunciation of the comforts of the world that Wittgenstein proposes as a way of coping with the brute contingencies of life seems only to come as far as what Kierkegaard calls 'infinite resignation', and this falls far short of the joyful acceptance of existence that appears necessary for inhabiting what Wittgenstein calls a happy world. That is to say, I will show that what Wittgenstein's proposal lacks is a way of reconnecting with the finite after one has renounced it – the kind of transformation of existence achieved by the person Kierkegaard calls the 'knight of faith'.